2021
DOI: 10.1038/s41598-021-87492-5
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mice overexpressing the LH receptor in the female reproductive system spontaneously develop endometrial tumour masses

Abstract: The receptor for the luteinizing hormone (LH-R) is aberrantly over expressed in cancers of the reproductive system. To uncover whether LH-R over expression has a causative role in cancer, we generated a transgenic (TG) mouse which overexpresses the human LH-R (hLH-R) in the female reproductive tract, under the control of the oviduct-specific glycoprotein (OGP) mouse promoter (mogp-1). The transgene was highly expressed in the uterus, ovary and liver, but only in the uterus morphological and molecular alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Recently, it was shown that knock-in mice expressing a constitutively activating LHR are infertile, presenting with anovulation, hormonal alterations and polycystic ovaries. Likewise, transgenic mice overexpressing the LH receptor in the female reproductive system spontaneously develop endometrial tumor [ 135 , 136 ].…”
Section: Influence Of Excessive Fsh Action On Testicular Functionmentioning
confidence: 99%
“…Recently, it was shown that knock-in mice expressing a constitutively activating LHR are infertile, presenting with anovulation, hormonal alterations and polycystic ovaries. Likewise, transgenic mice overexpressing the LH receptor in the female reproductive system spontaneously develop endometrial tumor [ 135 , 136 ].…”
Section: Influence Of Excessive Fsh Action On Testicular Functionmentioning
confidence: 99%
“…Until now, the possible direct effects of LH administration on endometrial receptivity and subsequent pregnancy rates remain controversial because of conflicting results from various human studies. To date, some studies have identified some beneficial effects of LH [ 57 60 ], whereas other studies have reported its adverse effects [ 18 , 61 , 62 ] on endometrial receptivity. In addition, according to several previous studies, it is known that the pregnancy rates of LH receptor knockout mice were reduced compared to normal mice [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the functional LH receptor (LHR), which was previously considered to be gonad tissue- or cell-specific, is highly expressed in the extragonadal endometrial tissue throughout the menstrual cycle [ 17 , 18 ]. It was recently observed that LH affects the uterine endometrium by promoting the differentiation of endometrial fibroblasts into fully differentiated decidual cells, which are essential for embryo implantation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclei were stained with Hoechst (1:1000 in PBS, 45 minutes; Merck Sigma). Images were captured using a Nikon TE2000 confocal microscope, as described in Lottini, et al, 2021 [ 59 ].…”
Section: Methodsmentioning
confidence: 99%